PD-1/PD-L1 inhibitors monotherapy vs. combination therapy in elderly advanced NSCLC: a real-world study and nomogram for survival prognosis - Yunye Mao; An Wang; Xiangwei Ge; Jinzhao Zhai; Yi Hu; Jinliang Wang (BMC Pulmonary Medicine)
Abstract Background Immunotherapy with PD-1/PD-L1 inhibitors has transformed advanced non-small cell lung cancer (NSCLC) treatment, yet optimal strategies for elderly patients remain uncertain. Elderly patients (≥ 65 years) exhibit immune senescence (e.g., T-cell dysfunction, chronic inflammation), which may compromise immunotherapy efficacy and amplify toxicity risks, yet direct comparisons of monotherapy versus combination regimens in this population are lacking. Real-world comparisons of monotherapy versus combination therapy in this vulnerable group are lacking, hindering personalized clinical decisions. Objective This real-world study aimed to compare the efficacy and safety of PD-1/PD-L1 inhibitor monotherapy versus combination therapy with chemotherapy in elderly patients (≥ 65 years) with advanced NSCLC and develop a prognostic nomogram to guide personalized treatment decisions. Methods In this multicenter retrospective study, 641 patients (149 monotherapy, 492 combination therapy) with stage IIIB/IV NSCLC were analyzed. Primary endpoints included overall survival (OS), progression-free survival (PFS), and adverse events (AEs). A nomogram incorporating clinical variables was constructed using LASSO-Cox regression. Results In a retrospective analysis of 641 elderly patients (≥ 65 years) with advanced NSCLC, combination therapy (n = 492) demonstrated superior median OS compared to monotherapy (n = 149) (35.37 vs. 20.53 months; HR = 0.62, 95% CI 0.48–0.80, P < 0.001), though PFS did not differ significantly (11.87 vs. 10.67 months; HR = 0.94, P = 0.535). Age-stratified analysis revealed marked OS benefits for patients < 75 years receiving combination therapy (36.10 vs. 18.67 months, P < 0.001), whereas no advantage was observed in those ≥ 75 years (29.23 vs. 34.93 months, P = 0.645). Cox regression identified combination therapy as a protective factor (HR = 0.54, P < 0.001), while ECOG PS ≥ 2 (HR = 1.87, P = 0.002), liver metastasis (HR = 1.62, P = 0.013), bone metastasis (HR = 1.84, P < 0.001), and malignant pleural effusion (HR = 1.64, P < 0.001) independently worsened prognosis. The incidence of AEs of any-grade (P < 0.001) and grade 3–4 (P = 0.003) in the immunotherapy combination group was significantly higher than that in the immunotherapy monotherapy group. A prognostic nomogram integrating treatment type, ECOG PS score, and other six variables had an AUC value of 0.70–0.71 for predicting 1–2 year OS. Conclusions For elderly patients with advanced NSCLC, immune combination therapy improved median OS over monotherapy. It was safe and effective, suggesting a viable treatment option, though further evaluation is needed for those aged 75 and older. A prognostic nomogram for OS following immunotherapy was developed, showing superior accuracy.